Pengendalian Hayati Penyakit Layu Fusarium Pisang (Fusarium oxysporum f.sp. cubense) dengan Trichoderma sp. - Albertus Sudirman; Christanti Sumardiyono; Siti Muslimah Widyastuti (Jurnal Perlindungan Tanaman Indonesia, 2011)
The aim of this research was to study the inhibiting ability of Trichoderma sp. to control fusarium wilt of banana in greenhouse condition. The experiments consisted of the antagonism test between Trichoderma sp. and Fusarium oxysporum f.sp. cubense (Foc) in vitro using dual culture method and glass house experiment which was arranged in 3×3 Factorial Complete Randomized Design. First factor of the latter experiment was the dose of Trichoderma sp. culture (0, 25, and 50 g per polybag), second factor was time of Trichoderma culture application (2 weeks before Foc inoculation, at same time with Foc inoculation and 2 weeks after Foc inoculation). Trichoderma sp. was cultured in mixed rice brand and chaff medium. The disease intensity was observed with scoring system of wilting leaves (0–4). The results showed that Trichoderma sp. was antagonistic against Foc in vitro and inhibited 86% of Foc colony development. Mechanism of antagonism between Trichoderma sp. and Foc was hyperparasitism. Trichoderma hyphae coiled around Foc hyphae. Lysis of Foc hyphae was occurred at the attached site of Trichoderma hyphae on Foc hyphae. Added banana seedling with Trichoderma sp. Culture reduced disease intensity of Fusarium wilt. Suggested dose of Trichoderma culture application in glass house was 25 g/polybag, given at the same time with Foc inoculation.